Determining grain resolved stresses in polycrystalline materials using three-dimensional X-ray diffraction - Oddershede, Jette; Schmidt, Søren; Poulsen, Henning Friis; Sørensen, Henning Osholm; Wright, Jonathan; Reimers, Walter (Journal of applied crystallography, 2010)
An algorithm is presented for characterization of the grain resolved (type II) stress states in a polycrystalline sample based on monochromatic X‐ray diffraction data. The algorithm is a robust 12‐parameter‐per‐grain fit of the centre‐of‐mass grain positions, orientations and stress tensors including error estimation and outlier rejection. The algorithm is validated by simulations and by two experiments on interstitial free steel. In the first experiment, using only a far‐field detector and a rotation range of 2 × 110°, 96 grains in one layer were monitored during elastic loading and unloading. Very consistent results were obtained, with mean resolutions for each grain of approximately 10 µm in position, 0.05° in orientation, and 8, 20 and 13 × 10−5 in the axial, normal and shear components of the strain, respectively. The corresponding mean deviations in stress are 30, 50 and 15 MPa in the axial, normal and shear components, respectively, though some grains may have larger errors. In the second experiment, where a near‐field detector was added, ∼2000 grains were characterized with a positional accuracy of 3 µm.